Supplemental progestin increases pregnancy rates in suckled beef cows - Lamb, G.C.; Cartmill, J.A.; Hensley, B.A.; El-Zarkouny, S.E.; Marple, T.J.; Stevenson, Jeffrey S.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In two experiments, combining a source of progestin with the ovulation synchronization protocol using gonadotropin-releasing hormone plus prostaglandin F2a (GnRH + PGF2a) tended to increase or statistically increase pregnancy rates in suckled cows compared to GnRH + PGF2a alone. These improvements were accomplished without any detected estrus when cows were inseminated and received a second injection of GnRH at 48 hr after PGF2a.
Keywords: Beef; Cows; AI; Estrus-Ovulation synchronization; GnRH; PGF2a; Progestin